Symptom control: using technology pragmatically - Richeimer, Steven (Henry Stewart Talks, 2009)
Use of PCA for acute or episodic pain, Blocks in cancer pain, Targeted analgesia, Use of continuous infusions, Neuroablative blocks, Spinal pumps: indications and benefits, Options for spinal pump medications, New option: Ziconotide, Managing the distressed patient best with a multidisciplinary team, Update interview: Update regarding opioids, Update interview: Ketamine and other NMDA antagonists, Update interview: Increased interest in interventional techniques and implants, Update interview: The importance of multidisciplinary teams in pain medicine
Updated at 2020/08/14